Collaboration in the wood biomass supply chain for the circular economy: findings from empirical research - Kawa, Arkadiusz (Journal of Management and Financial Sciences, 2026)
Amid growing pressure to implement the principles of the circular economy, the wood biomass sector provides an important area in which it is possible to examine supply chain collaboration. This study aims to explore current collaboration between different actors in the management of wood residues, and to identify the challenges and opportunities for enhancing circularity. Focus group interviews were conducted with representatives from sawmills, wood manufacturers, logistics firms and energy companies. The analysis covered material flows, sorting practices, value recovery strategies and collaboration mechanisms. The findings reveal formal and informal cooperation practices, as well as key barriers such as transport costs, a lack of standardisation, and limited system integration. Participants identified potential solutions, including exchange platforms, shared logistics and fiscal incentives. The study makes recommendations to support the development of circular supply chains and argues that deeper cross-sector coordination, investment in enabling infrastructure, and improved information flow are critical to closing the loop in the wood biomass domain.